2013
DOI: 10.1007/s00586-013-2916-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided versus computed tomography-controlled periradicular injections in the middle and lower cervical spine: a prospective randomized clinical trial

Abstract: Purpose We conducted this study to evaluate accuracy, time saving, radiation doses, safety, and pain relief of ultrasound (US)-guided periradicular injections versus computed tomography (CT)-controlled interventions in the cervical spine in a prospective randomized clinical trial. Methods Forty adult patients were consecutively enrolled and randomly assigned to either a US or a CT group. USguided periradicular injections were performed on a standard ultrasound device using a broadband linear array transducer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 25 publications
1
31
0
3
Order By: Relevance
“…Licz ne pu bli ka cje pod kre śla ją wy so ką sku tecz ność tech ni ki ul tra so no gra ficz nej kon tro li in iek cji oko ło krę go wych, pod kre śla jąc jedno cze śnie ich bez pie czeń stwo i brak ró żnic w wy nikach le cze nia. Dzię ki znacz nej zbie żno ści kost nych mar ke rów ana to micz nych ob ser wo wa nych w USG z prze kro ja mi CT i ba da nia mi sek cyj ny mi, in iek cje oko ło krę go we wy ko ny wa ne pod kon tro lą USG charak te ry zu ją się wy star cza ją cą do kład no ścią i wia rygod no ścią lo ka li za cji igły w opar ciu o cha rak te rystycz ne prze kro je ob ry sów kost nych [22,23]. W ni niejszym opra co wa niu te ra pia bio lo gicz na ACS utrzy muje swo ją sku tecz ność na wet po 3 mie sią cach od po dania ostat niej daw ki su ro wi cy, w od ró żnie niu od te ra pii ste ry do wej, gdzie zgod nie z far ma ko dy na mi ką pre para tów ob ser wu je się za nik efek tu prze ciw bó lo we go i prze ciw o brzę ko we go już po 3 do 6 ty go dniach.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Licz ne pu bli ka cje pod kre śla ją wy so ką sku tecz ność tech ni ki ul tra so no gra ficz nej kon tro li in iek cji oko ło krę go wych, pod kre śla jąc jedno cze śnie ich bez pie czeń stwo i brak ró żnic w wy nikach le cze nia. Dzię ki znacz nej zbie żno ści kost nych mar ke rów ana to micz nych ob ser wo wa nych w USG z prze kro ja mi CT i ba da nia mi sek cyj ny mi, in iek cje oko ło krę go we wy ko ny wa ne pod kon tro lą USG charak te ry zu ją się wy star cza ją cą do kład no ścią i wia rygod no ścią lo ka li za cji igły w opar ciu o cha rak te rystycz ne prze kro je ob ry sów kost nych [22,23]. W ni niejszym opra co wa niu te ra pia bio lo gicz na ACS utrzy muje swo ją sku tecz ność na wet po 3 mie sią cach od po dania ostat niej daw ki su ro wi cy, w od ró żnie niu od te ra pii ste ry do wej, gdzie zgod nie z far ma ko dy na mi ką pre para tów ob ser wu je się za nik efek tu prze ciw bó lo we go i prze ciw o brzę ko we go już po 3 do 6 ty go dniach.…”
Section: Discussionunclassified
“…Numerous publications stress the high efficacy of ultrasound guidance of perivertebral injections, pointing out their safety and the lack of differences in treatment outcomes. Due to the considerable similarity between ana tomical bone landmarks observed in an ultra sound study and those found on CT cross-sections and in autopsy examinations, perivertebral injections performed under ultrasound guidance are characterised by sufficient accuracy and reliability of needle location based on characteristic bone outline cross-sections [22,23]. In the present study, the efficacy of the biological therapy with ACS was maintained even at 3 months after the administration of the last dose of the serum, as opposed to steroid therapy, where, in accordance with the pharmacodynamics of the preparations, the analgesic and anti-inflammatory effects wear off after 3-6 weeks.…”
Section: Wnio Skimentioning
confidence: 99%
“…There is increasing concern about the effects of radiation now that various MISS procedures are increasingly used, so the paper by Obernauer et al [57] reporting a prospective randomised trial comparing the use of ultrasound with CT guided periradicular injections in the middle and lower cervical spine is of some interest. The needle was guided by ultrasound, and the final position verified by CT in one group, and in the other CT was used throughout the procedure.…”
Section: Cervical Spinementioning
confidence: 99%
“…In particular, according to several authors [12][13][14][15][16], US is at least sufficiently reliable and accurate in the demonstration of cervical paravertebral anatomy, facilitating the localization and imaging of muscles, superficial ligaments, spinal nerve roots, vessels, as well as bony landmarks and interarticular space of facet and articular joints. This is of clinical relevance because these structures can possibly be used as ''imaging'' landmark for therapeutic purposes [14][15][16][17] as demonstrated while performing image-guided injections (for nerves or articular pathologies) of the cervical spine [18,19]. In particular, it has been reported that US, when compared to fluoroscopy or CT, is an excellent tool for ''visualizing'' (accuracy 68-100 %) and hence ''avoiding'' vascular injury during interventional procedures [18], whereas fluoroscopy can only ''detect'' that the tip of the needle is intravascular (after the fact) [20].…”
Section: Discussionmentioning
confidence: 99%